Integrated sedimentology and micropaleontology for the study of the deglaciation post LGM in the south- western Svalbard slope (Arctic Ocean). - Katia Carbonara; Renata Giulia Lucchi; Romana Melis; Karin Mezgec; Caterina Morigi; MUSCO, MARIA ELENA; Gabriella Varagona; Giuliana Villa (Rendiconti Online della Società Geologica Italiana, 2016)
The north-western continental margin of the Barents Sea represents the only gateway for deep-water masses moving between the North Atlantic and the Arctic Oceans. On this respect, the western Svalbard margin, located on the eastern side of the Fram strait straight, represents a key area to study the paleoceanographic variation of the North Atlantic/West and East Spitsbergen currents . Integrated sedimentological and micropaleontological analyses on calcareous nannofossils, diatoms, planktonic and benthonic foraminifera and clay mineral assemblages have been performed on three sediment cores, collected during the EGLACOM and CORIBAR projects from the Storfjorden-Kveithola depositional system (NW Barents Sea), to with the aim of reconstructing the deep-water paleoceanographic evolution after the Last Glacial Maximum. The lithological sequence and the magnetic susceptibility are consistent between the EGLACOM and CORIBAR cores. The recovered cores contain an expanded thick sedimentary sequence that includes continuous well-preserved Holocene interglacial sediments. The microfossils are scarce in the lithological units that represent the deglaciation after LGM, and became abundant in the Holocene sequences that record a clear upswingreprise of the North Atlantic Current (NAC) strength. AnywayNevertheless, the benthic assemblage is indicative of non-permanently ice-covered conditions since about 16 cal ka BP. The planktonic microfossil patterns of distribution are coherent with the trend of smectite content in the clay mineral assemblage that is mainly transported by the NAC, therefore high contents are associated to a vigorous current (Junttila et al., 2010). The nannofossil assemblages during the Holocene, are dominated by Emiliania huxleyi (< 4 µm), confirming the climatic ameliorationdeglaciation trend. The diatom assemblages are dominated by Chaetoceros resting spores, related to stratified waters in association with ice melting at the beginning of Holocene. The presence of the diatom Coscinodiscus spp. and a ...